Teacher Human Resource Management for Aqidah-Akhlaq: Implementing Active Learning Strategies at Madrasah Ibtidaiyah - Ana Raudlatul Janah; Nurfuadi Nurfuadi (Lembaga Yasin AlSys, 2026)
Islamic education, particularly the Aqidah-Akhlaq (Creed and Morals) subject, continues to face challenges from conventional teacher-centered approaches that constrain student engagement and limit moral internalization. This study examines the role of teacher human resource management (HRM) in implementing active learning strategies at MI Ma’arif NU Langkap, with the aim of analyzing how HRM processes support pedagogical innovation in Aqidah-Akhlaq and contribute to holistic character formation. Employing a qualitative descriptive design, data were collected through in-depth interviews, participant observations, and document analysis from purposively selected informants, including teachers, school leaders, and key stakeholders. Data were analyzed using Miles and Huberman’s interactive model—encompassing data condensation, data display, and conclusion drawing—with credibility ensured through triangulation of sources and methods. The findings reveal a systematic HRM cycle comprising planning (competency mapping and identification of training needs), development (workshops on active strategies such as discussion, simulation, and peer teaching), implementation (student-centered activities that enhance participation and value application), and evaluation (continuous supervision and feedback). This cycle significantly improved teachers’ pedagogical quality and shifted classroom practice from passive memorization toward experiential engagement that integrates cognitive, affective, and behavioral dimensions. Active learning in Aqidah-Akhlaq was found to align closely with the profiles envisioned in Profil Pelajar Pancasila, reinforcing values-based competencies. The study concludes that strategic HRM is pivotal for sustaining active learning in Islamic education and recommends ongoing professional development, the use of digital tools for monitoring and evaluation, and policy support to facilitate broader replication in madrasahs. These findings provide theoretical insights into HRM-driven pedagogical reform and practical guidance for strengthening Islamic character education at the Madrasah Ibtidaiyah level.